Regulasi Pertanggungjawaban Hukum Pelaku Tindak Pidana Pembalakan Liar dan Penyelundupan Ekspor Kayu Bakau - Deaf Wahyuni Ramadhani (Universitas Kuningan, 2024)
Mangrove forests in Indonesia constitute 23% of the world's mangrove ecosystem. This study aims to analyze the Regulation of Legal Responsibility of Criminal Acts of Illegal Logging and Smuggling of Mangrove Wood Exports in Indonesia. This research method is a doctrinal legal research with a case approach; secondary data sources are obtained from library materials; data collection techniques are carried out by literature studies; all data collected will be analyzed deductively. The results of the study are the Regulation of Legal Responsibility of Criminal Acts of Illegal Logging and Smuggling of Mangrove Wood Exports in Indonesia in Law Number 17 of 2006 concerning Customs. Law No. 41 of 1999 concerning Forestry. Law No. 18 of 2013 concerning Prevention and Eradication of Forest Destruction. The conclusion is that the regulations regarding illegal logging and smuggling of mangrove wood exports are complete. The judge's suggestion has considered the sustainability of Natural Resources but has not been oriented towards the preservation of the mangrove ecosystem and the criminal penalties applied must be maximal.